Delivery of the National Child Measurement Programme in England. Issue 6 (9th April 2021) - Čadek, Martin; Flint, Stuart W; Tench, Ralph
Abstract: Objective: The National Child Measurement Programme (NCMP) is a mandatory initiative delivered in England to children in Reception and Year 6. To date, no research has explored the methods used to deliver the NCMP by Local Government Authorities (LGA) across England. Design: An online survey was administered between February 2018 and May 2018 to explore the delivery of the NCMP across the 152 LGA in England and disseminated using non-probability convenience sampling. Setting: LGA received an anonymous link to the survey. Participants: A total of 92 LGA participated in the survey. Results: Most LGA who responded provide result feedback (86 %), a proactive follow-up (71 %) and referrals to services (80 %). Additionally, 65 % of the authorities tailor Public Health England specimen result letters to suit their needs, and 84 % provide attachments alongside. Out of 71 % of LGA who provide proactive follow-up, 19 (29 %) provide the proactive follow-up only to upper weight categories and only 4 (6 %) include Healthy Weight category with other categories in proactive follow-up. Regarding the service availability for children, out of 80 % of LGA who indicated that services are available, 32 (43 %) targeted solely upper weight categories, while the other 42 (57 %) offered services across all weight categories. Finally, most LGA (88 %) commission providers to manage various parts of the NCMP. Conclusions: The results show that LGA in England localise the NCMP. Further guidance regarding standards of best practice would help LGA to find the most suitable localisation out of various options that exist across other LGA.